Therapeutic schoolyard: design for children with autism - King, Chelsey (Kansas State University, 2012)
It is estimated by the Center for Disease Control and Prevention that approximately 1 in every 88 children are diagnosed with some level of autism or various degrees of Pervasive Developmental Disorders (2012). Pervasive Developmental Disorders are commonly referred to as Autism Spectrum Disorders (and hereafter referred to as autism). Many children with autism have difficulty communicating, must cope with their disorder, and may need special considerations in the classroom. Needs of children with autism vary from child to child, but they all can benefit from environments that are designed with awareness of challenges and characteristics associated with autism. Schoolyards commonly contain asphalt, turf, and traditional play structures that do not take into consideration the needs of children with mental or physical disabilities. However, schoolyards can be designed to provide therapeutic benefits on these children without segregating them from the larger school community. In order to understand how a schoolyard might be designed as a therapeutic environment for children with autism the challenges, needs, and common therapies for children with autism must be understood. The characteristics of therapeutic landscapes for children must be considered in addition. After examining both therapeutic landscapes and the many facets of autism, the researcher applied lessons learned to the design of a schoolyard master plan for Amanda Arnold Elementary School in Manhattan, Kansas.
Keywords: Landscapes of Learning; Schoolyard Design; Autism; Therapeutic Landscapes; Landscape Architecture (0390)